The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s1516-89132008000400024
|View full text |Cite
|
Sign up to set email alerts
|

Localization and partial characterization of thermostable glucoamylase produced by newly isolated Thermomyces lanuginosus TO3 in submerged fermentation

Abstract: Thermophilic Thermomyces lanuginosus strain TO3 was isolated from compost pile samples and was used for its ability to produce considerable glucoamylase activity when growing in liquid medium at 45ºC with starch as the sole carbon source. Enzyme productivity was high in submerged fermentation (SmF) with maximum activity of 13 U/mL after 168 h of fermentation. Higher quantities of glucose were released when the substrate for enzyme was soluble starch than maltose or maltooligosaccharides were used. The distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…This optimization strategy led to the enhancement of glucoamylase production from 4.57 U/mL (unoptimized medium) to 12.27 U/mL (optimized medium), a 2.68-fold increase. In addition to this, the optimized glucoamylase activity was found to be higher than the available literature value for various thermophilic fungi such as Scytalidium thermophilum 15.8 (3.62 U/mL) [ 26 ], Thermomyces lanuginosus A.13.37 (2.8 U/mL) [ 2 ], and Thermomyces lanuginosus ATCC 200065 (7.4 U/mL) [ 27 ] and comparable with Thermomyces lanuginosus TO3 (13 U/mL) [ 28 ].…”
Section: Resultsmentioning
confidence: 98%
“…This optimization strategy led to the enhancement of glucoamylase production from 4.57 U/mL (unoptimized medium) to 12.27 U/mL (optimized medium), a 2.68-fold increase. In addition to this, the optimized glucoamylase activity was found to be higher than the available literature value for various thermophilic fungi such as Scytalidium thermophilum 15.8 (3.62 U/mL) [ 26 ], Thermomyces lanuginosus A.13.37 (2.8 U/mL) [ 2 ], and Thermomyces lanuginosus ATCC 200065 (7.4 U/mL) [ 27 ] and comparable with Thermomyces lanuginosus TO3 (13 U/mL) [ 28 ].…”
Section: Resultsmentioning
confidence: 98%
“…lanuginosus is an interesting fungus because it can produce enzymes of industrial interest such as invertase (Chaudhuri and Maheshwari, 1996), β-xylosidase (Corrêa et al, 2016), chitinase (Khan et al, 2015;Chen et al, 2012;Zhang et al, 2015), protease (Li et al, 1997), inulinase (FloresGallegos et al, 2015), esterase , amylase (Kunamneni et al, 2005), glucoamylase (Gonçalves et al, 2008), α-galactosidase (Rezessy-Szabó et al, 2007), and the two most reported enzymes, lipase Ávila-Cisneros et al, 2014;Fang et al, 2014) and xylanase Stephens et al, 2014;Shrivastava et al, 2013;Manimaran et al, 2009). Furthermore, T. lanuginosus is known for producing cellulase-free xylanases (Manimaran et al, 2009;Li et al, 2005;Damaso et al, 2002).…”
Section: T Lanuginosusmentioning
confidence: 99%